2004
DOI: 10.1182/blood-2003-08-2978
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell–mediated inflammatory responses require the α2β1 integrin

Abstract: Although the ␣2␤1 integrin is widely expressed and has been extensively studied, it has not been previously implicated in mast cell biology. We observed that ␣2 integrin subunit-deficient mice exhibited markedly diminished neutrophil and interleukin-6 responses during Listeria monocytogenes-and zymosan-induced peritonitis. Since exudative neutrophils of wildtype mice expressed little ␣2␤1 integrin, it seemed unlikely that this integrin mediated neutrophil migration directly. Here, we demonstrate constitutive ␣… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 52 publications
4
78
0
Order By: Relevance
“…In our model, mice reconstituted with Camp ϩ/ϩ cells inhibited edema to a higher extent than the mice reconstituted with Camp Ϫ/Ϫ MC, indicating that cathelicidin might have a modulating effect on the antiinflammatory cytokine production. Moreover, we were able to confirm previous observations that MC are able to modulate neutrophilic infiltration (8,11,51). This effect may be partially modified by the presence of cathelicidin inside MC.…”
Section: Discussionsupporting
confidence: 80%
“…In our model, mice reconstituted with Camp ϩ/ϩ cells inhibited edema to a higher extent than the mice reconstituted with Camp Ϫ/Ϫ MC, indicating that cathelicidin might have a modulating effect on the antiinflammatory cytokine production. Moreover, we were able to confirm previous observations that MC are able to modulate neutrophilic infiltration (8,11,51). This effect may be partially modified by the presence of cathelicidin inside MC.…”
Section: Discussionsupporting
confidence: 80%
“…As shown in Fig. 3A, 3-4% of crude peritoneal cells expressed both CD117 and CD49b, and these double-positive cells were considered as PMC, as previously reported by us and others (46,52). As shown in Fig.…”
Section: Flow Cytometry Analyses Of Tlr4 and Tlr9 Expression By Mast mentioning
confidence: 89%
“…The reduced levels of RANKL and osteoclast numbers by a2b1 integrin mAb in IL-7-treated mice can be attributed at least to the reduction of IL-17 levels because IL-17 is a strong inducer of RANKL in stromal cells and osteoblasts (4, 5, 44). Although IL-7/IL-7R signaling has recently been involved in myeloid cells of RA (18), it is unlikely that the blockade of IL-7-induced bone loss by anti-a2b1 mAb occurs at the level of myeloid cells because a2b1 integrin expression is not associated with neutrophils or monocytic/macrophage lineage (45)(46)(47), which constitutes the main source of osteoclast precursors. In addition, previous studies and recent evidence from the a2b1 integrindeficient mice indicated that although osteoclasts may express a2b1 integrin, it seems that their function depends more on avb3 integrin rather than on a2b1 and other integrins (48,49).…”
Section: Discussionmentioning
confidence: 99%